A rare presentation of a paediatric sinonasal inverted papilloma. Issue 11 (30th November 2018) - Jayakody, Nimeshi; Ward, Matthew; Wijayasingham, Giri; Fowler, Darren; Harries, Philip; Salib, Rami
Abstract: Sinonasal inverted papilloma (IP) is a benign tumour with an extremely low incidence in children. We report the case of an 11-year-old Caucasian male presenting with recurrent right-sided epistaxis, nasal obstruction and a mass in the right nasal cavity. An initial diagnosis of a nasopharyngeal angiofibroma was considered; however, on detailed histological examination, the mass was found to be an inverted papilloma. This report aims to increase awareness of IP in the paediatric age group, as well as reinforcing the role of endoscopic surgery in the management of this condition.